Piezoelectric characterization of Sc0.26Al0.74N layers on Si (001) substrates. (14th March 2018) - Sinusía Lozano, M; Pérez-Campos, A; Reusch, M; Kirste, L; Fuchs, Th; Žukauskaitė, A; Chen, Z; Iriarte, G F
Abstract: Scandium aluminum nitride (ScAlN) films have been synthesized by pulsed-DC reactive magnetron sputtering. The degree of c -axis orientation as well as piezoelectric characteristics of the Sc0.26 Al0.74 N thin films grown on Si (001) at various discharge powers and processing pressures values have been investigated. According to x-ray diffraction (XRD) measurements, the texture of the as-grown Sc0.26 Al0.74 N thin films becomes more prominent in the [0001]-direction at the highest target power (700 W) and at the lowest processing pressure (4 mTorr). The piezoelectric response, as determined by measuring the d33 piezoelectric constant, shows a maximum value of −12 pC/N also at 4 mTorr and 700 W, confirming a direct correlation between the d33 piezoelectric constant and the degree of orientation in the [0001]-direction. The atomic concentration of Sc and Al in the synthesized ScAlN thin film, determined by secondary ion mass spectroscopy (SIMS), reveals a Sc concentration lower than in the ScAl alloy target. The piezoresponse force microscopy (PFM) shows homogeneous polarity distribution with no inversion domains. The piezoelectric layers have been used to fabricate and measure surface acoustic wave (SAW) resonators on a Sc0.26 Al0.74 N/Si (001) bilayer system with resonance frequency of 1.4 GHz and coupling coefficient of 0.567. Such characteristic in the frequency response reveals the potential of these materials for advanced SAW devices in applications such as next generation (5 G) wireless communication systems.